The syndrome of pneumococcemia, disseminated intravascular coagulation and asplenia. - Kingston, M E (1979)
A 58-year-old man who survived an episode of fulminant pneumococcal septicemia with disseminated intravascular coagulation had undergone splenectomy 23 years previously. In the literature there are 25 reported cases of fulminant septicemia and disseminated intravascular coagulation associated with asplenia in adults (excluding cases in which corticosteroid or immunosuppressive therapy was given). The pneumococcus was responsible for all of these cases as well. The mortality in this series was more than 90%, and death occurred within 24 hours of presentation at hospital in almost 70% of the fatal cases and was associated with high-density bacteremia and adrenal hemorrhage. Gram-staining of the buffy coat of the peripheral blood or the exudate from purpuric skin lesions was carried out in only 6 of the 26 cases but yielded positive results in all but 1. It is concluded that a diagnosis of septicemia in asplenic adults can be established within a short time of presentation on the basis of statistical probability and the results of Gram-staining of the peripheral blood and exudate from the skin lesions. Prevention appears to be the cornerstone of management because of the variable interval from splenectomy to the onset of the syndrome and the high mortality.